TRADISI AIR MANUK: KAJIAN SEJARAH DAN PENDIDIKAN ISLAM DI PULAU KUR KOTA TUAL - Abd Rahim Letsoin; Nurleli Ramli; Sahril Rumagorong; Warwefubun, Jamain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Air Manuk Tradition is one of the cultural heritages of the people of Kur Island, Tual City, which continues to be preserved as an integral part of their social, religious, and historical identity. This tradition is not merely regarded as a customary ritual but also serves as a medium for transmitting Islamic values from one generation to another through prayers, dhikr, hadarah recitations, and respect for ancestors as well as Islamic figures who contributed to the spread of Islam in the region. This study aims to examine the historical origins of the Air Manuk Tradition and to analyze the Islamic educational values embedded within it. The research employed a qualitative method with historical and ethnographic approaches. Data were collected through field observations, in-depth interviews with customary leaders, religious leaders, and local community members, as well as documentation studies related to the implementation of the tradition. The findings reveal that the Air Manuk Tradition is closely connected to the process of the arrival and development of Islam on Kur Island through missionary activities, trade networks, and cultural interactions. The tradition embodies various Islamic educational values, including religiosity, respect for ancestors, Islamic brotherhood (ukhuwah Islamiyah), mutual cooperation, social solidarity, moral responsibility, and spiritual development for younger generations. In addition to functioning as a symbol of the cultural identity of the Kur Island community, the Air Manuk Tradition also serves as a means of preserving local Islamic history and strengthening Islamic character within society. Therefore, this tradition plays a significant role in maintaining the continuity of cultural heritage and Islamic educational values amidst the challenges of modernization and globalization.